Acute Oral Toxicity - Rao, K.S. (Biology, Engineering, Medicine and Science Reports)
I am covering this simple and mundane acute tox- icity test to increase the awareness, understanding and an appreciation of acute toxicity test, which has undergone sea-change in the last decade. In this commentary, I am not going to discuss details of dif- ferent OECD guidelines which any one can down- load from the OECD website.